T1 Loss of BAP1 function leads to TRAIL sensitivity in mesothelioma. (December 2018) - Kumar, N; Kolluri, KK; Alifrangis, C; Ishii, Y; Price, S; Michaut, M; Williams, S; Barthorpe, S; Lightfoot, H; Busacca, S; Sharkey, A; Yuan, Z; et al.
Abstract : Introduction: Malignant mesothelioma (MM) has no biomarker driven therapies in routine clinical use. We used a drug screen of molecularly characterised MM lines to identify novel genomic biomarker driven therapy. This led to the discovery of a subset of MMs, defined by loss of function (LOF) of the nuclear deubiquitinase BRCA associated protein 1 (BAP1), that demonstrate heightened sensitivity to tumour necrosis factor related apoptosis inducing ligand (TRAIL). We then validated this association across in vitro, in vivo and ex vivo models and delineated the underlying mechanism. Methods: 15 MM lines were characterised for mutations in five MM tumour driver genes and screened for response to 95 compounds. The identified BAP1-TRAIL association was validated in an extended panel of MM lines with apoptosis and cell viability assays. 25 early passage MM cultures, mouse xenograft and human tumour explant models were used to further validate the association. Knock-in and knock-out models in BAP1 mutant and wild type lines confirmed the effect of loss of BAP1 expression on TRAIL sensitivity. 6 mutant BAP1 constructs were generated and identified which functional BAP1 sites modulate TRAIL sensitivity. The effect of BAP1 function on the downstream death receptor/apoptosis pathway components was determined using microarray and immunoblot analysis. Results: BAP1 LOF significantly correlated with TRAIL sensitivity in established MM lines (p=0.015) and primary MM cultures (p<0.0064). This association was confirmed in mouse xenograft (p<0.05) and tumour explant models. Mutagenesis of BAP1 confirmed deubiquitinase activity and its ability to bind to ASXL proteins to form the polycomb repressor deubiquitinase complex (PR-DUB) as determinants of TRAIL sensitivity, implicating modulation of transcriptional programmes as an underlying mechanism. Consistent with this, knockdown of ASXL1 also increased TRAIL sensitivity in MM lines and loss of BAP1 deubiquitinase and ASXL binding activity altered gene, and protein expression of components of the apoptotic machinery favouring apoptosis upon activation of death receptors. Conclusions: We identify loss of BAP1 as a novel biomarker for TRAIL sensitivity in MM. BAP1 LOF is observed in up to 67% of MM tumours and BAP1 immunohistochemistry is in use as a diagnostic tool; hence this approach is validated and ready for immediate and actionable clinical use for this disease.